Utilization of rice bran in chocolate chip cookies - Castellano, Maureen Torres
Incorporation of rice bran in cookies has never been studied in detail before. This research paper, therefore, serves as a guide and introduction to those food manufacturers interested in reducing cost of cookies be checking rice bran-flour mixture. The utilization of rice bran in the production of chocolate chip cookies was undertaken. Studies in the shelf-life and the nutritive qualities of the resulting product were also done. Phase I of the study dealt primarily on the determination of the most acceptable level of rice bran incorporation using the amount of flour as a basis. Sensory evaluation of products with increasing levels of incorporation showed that at 25% incorporated rice bran, no difference can be found when compared to a control of 0% rice bran. Phase II was a storage study of the acceptable rice bran level. Subjective and objective tests were done in conjunction with the storage study. Final analysis indicate that the cookies, upon storage in a plastic rigid container, have an estimated shelf-life of 9 days at room temperature, 2 days at 37°C and 4 days at 55°C. Phase III utilized proximate analysis to evaluate the products nutritive composition. Comparison of % composition showed that the product is at par with existing cookie products.